What kind of cotton ideotype is adapted to agroecological cropping systems and climate change in Benin? - Dègbédji Charlemagne Aboua; Edward Gérardeaux; Philippe Debaeke; Stéphane Boulakia; Emmanuel Sekloka (Journal of Cotton Research)
Abstract Background Agroecological cropping systems are recognised as an alternative way to ensure the sustainability of cotton (Gossypium hirsutum L.) production in the context of climate change and degradation of soil fertility. A study was conducted in Benin from 2020 to 2023 to compare six different cotton cultivars in three agroecological cropping systems in two cotton-growing zones. Plough-based tillage plus incorporation of cover crop biomass (PTI), conservation agriculture with strip tillage (CA_ST), and conservation agriculture with no tillage (CA_NT) were compared with the reference plough-based tillage (PT). The objective was to identify morpho-physiological traits of cotton that increase yield in agroecological cropping systems. Our approach combined a field experiment and crop simulation model (CSM) of CROPGRO-Cotton to evaluate the effects of genotype (G) × environment (E) × management (M) interactions on seed cotton yield (SCY). Results Cultivars Tamcot_camde and Okp768 and simulated ideotypes performed best in CA systems. Increased seed mass, large and thick leaves, and later maturity were identified as beneficial for yield enhancement in CA systems. Cultivars and ideotypes that combine these traits also resulted in better nitrogen and water use efficiencies in CA systems. Under different climate scenarios up to 2050, ideotypes designed could increase SCY in Benin. Conclusion A set of morpho-physiological traits associated with vegetative vigour is required to ensure a good SCY in agroecological cropping systems. These results provide scientific evidence and useful knowledge for breeders and research programmes on cropping systems focused on the adaptation of cotton to climate change.